Kepentingan Jepang Melalui JICA Terhadap Pemberian Bantuan Proyek DSDP di Indonesia - Tular, Bianda Evania; Priadarsini, Ni Wayan Rainy; Widyanugraha, Anak Agung Bagus Surya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2016)
ABSTRACT This study was made after an  issue about Japan’s interests through JICA (Japan International Cooperation Agency) with the loan aid to Indonesia in DSDP (Denpasar Sewerage Development Project) Project Bali, Indonesia. DSDP is the first sanitation project in Indonesia that the research was conducted by JICA and the loan aid was given from Japan. This mega project could say as one of many ways to accomplish Japan's interest in Indonesia. Many reasons make this research happen, some of them are the difference of Indonesia’s respond to both of the ex-colonial country, Netherland and Japan, through the aid project and also JICA persuasive approach that becoming suspicious if there is a bigger reason behind this realization of this project. The goals of this study is to show the reader about Japan’s interest clearly by the realization of this project. Keywords :JICA, DSDP,  National Interest, aid, state agency